Coronary artery disease in women - Duda-Pyszny, Dominika (Kardiochir Torakochirurgia Pol, 2018)
Cardiovascular diseases, including coronary artery disease (CAD), are the leading cause of death among women and men. Mortality among women is higher than in men. Women more often report atypical anginal symptoms. Non-invasive diagnostic testing of CAD is less sensitive and characteristic in women than in men. Coronary angiography and rewascularization of coronary arteries is less common in women. However, women, who undergo angiography have lower rates of obstructive CAD. The worse prognosis of CAD in women is associated with the fact that the onset of obstructive coronary artery disease in women occurs 7–10 years later than in men. Older women are also more often burdened with comorbidities. The aim of this study was to compare the clinical characteristics, diagnostics, and treatment of CAD in women and men.